Stereoselective cyclo-addition reactions of azomethine ylides catalysed by in situ generated Ag(I)/bisphosphine complexes - VLADIMIR SAVIĆ (Journal of the Serbian Chemical Society, 2010)
Stereoselective cyclo-addition reactions of azomethine ylides promoted by in situ generated Ag(I)/bisphosphine complexes were studied. Under the optimised conditions, the pyrrolidine products were isolated in up to 84 % yield and with up to 71 % e.e. The effects of various reaction variables on the stereoselectivity were also investigated.